The Most Influential Factors of Hypertension Grade Among Patients Aged 45-75 In the Community Health Center of North Kediri City - Radono, Panca; Samuel Kaka; Dhita Kurnia Sari; Donny Irawan; Andica Apriannisa (Universitas STRADA Indonesia, 2024)
Hypertension, often referred to as the silent killer, is a deadly disease that often shows no symptoms until it is too late. Understanding the factors that contribute to its incidence is crucial. In this observational cross-sectional study, 263 hypertensive patients aged 45-75 years were examined to determine the influential factors. Using purposive sampling, a sample of 42 respondents was chosen. The independent variables studied were diet and activity patterns, while the dependent variable was the occurrence of hypertension. The statistical analysis was conducted using ordinal regression. The findings revealed that 64.3% of hypertensive patients aged 45-75 years had an improper diet, while 45.2% had poor activity patterns. Grade I hypertension was observed in 40.5% of the respondents. The data analysis indicated a significant influence of diet, activity, and hypertension (p = 0.00 < α = 0.05). Furthermore, the wald value of 17,286 suggested that diet had a greater impact. The study concluded that diet was the most influential factor, emphasizing the importance of avoiding high-cholesterol foods (e.g., fried and coconut milk-based dishes), fatty meats, and high-salt foods (e.g., pickles). These findings highlight the need for individuals to be mindful of their dietary choices to prevent and manage hypertension effectively.